A Novel Methodology for Identifying Cross-Country Faults in Series-Compensated Double Circuit Transmission Lines - Singh S.; Vishwakarma D.N. (My University, 2025)
In this paper, a competent mechanism for classifying cross-country faults in series-compensated (SC) double circuit transmission line (DCTL) is presented. Cross-country faults are usually different from frequently occurring short-circuit faults in the transmission system. The faults that strike up at the same time but on different positions in the transmission network and can involve same or different phases are termed as cross-country faults. An occurrence of such abnormality in the transmission network significantly hampered the functioning of traditional distance relaying. This paper presents a novel methodology for discriminating normal short-circuit faults and cross-country faults in SC double circuit power network based on empirical mode decomposition (EMD) and intelligent technique. The efficacy of the proposed mechanism for discriminating normal short-circuit faults and cross-country faults in the series-compensated DCTL system, various cases of normal short-circuit faults and cross-country faults (with varying system conditions) have been simulated in Real Time Digital Simulator (RTDS). The results acquired after performing several test cases reveal the practicability of applying proposed EMD and intelligent techniques based mechanism for classification of cross-country faults from normal short-circuit abnormality in the transmission network. © 2018 The Authors. Published by Elsevier B.V.